Socioeconomic and Tobacco Mediation of Ethnic Inequalities in Mortality over Time: Repeated Census-mortality Cohort Studies, 1981 to 2011. Issue 4 (July 2018) - Blakely, Tony; Disney, George; Valeri, Linda; Atkinson, June; Teng, Andrea; Wilson, Nick; Gurrin, Lyle
Abstract : Background: Racial/ethnic inequalities in mortality may be reducible by addressing socioeconomic factors and smoking. To our knowledge, this is the first study to estimate trends over multiple decades in (1) mediation of racial/ethnic inequalities in mortality (between Māori and Europeans in New Zealand) by socioeconomic factors, (2) additional mediation through smoking, and (3) inequalities had there never been smoking. Methods: We estimated natural (1 and 2 above) and controlled mediation effects (3 above) in census-mortality cohorts for 1981–1984 (1.1 million people), 1996–1999 (1.5 million), and 2006–2011 (1.5 million) for 25- to 74-year-olds in New Zealand, using a weighting of regression predicted outcomes. Results: Socioeconomic factors explained 46% of male inequalities in all three cohorts and made an increasing contribution over time among females from 30.4% (95% confidence interval = 18.1%, 42.7%) in 1981–1984 to 41.9% (36.0%, 48.0%). Including smoking with socioeconomic factors only modestly altered the percentage mediated for males, but more substantially increased it for females, for example, 7.7% (5.5%, 10.0%) in 2006–2011. A counterfactual scenario of having eradicated tobacco in the past (but unchanged socioeconomic distribution) lowered mortality for all sex-by-ethnic groups and resulted in a 12.2% (2.9%, 20.8%) and 21.2% (11.6%, 31.0%) reduction in the absolute mortality gap between Māori and Europeans in 2006–2011, for males and females, respectively. Conclusions: Our study predicts that, in this high-income country, reducing socioeconomic disparities between ethnic groups would greatly reduce ethnic inequalities in mortality over the long run. Eradicating tobacco would notably reduce ethnic inequalities in absolute but not relative mortality. Abstract : Supplemental Digital Content is available in the text.